(untitled) (PerCursos, 2022)
The 1990s reveal important movements in geographer Milton Santos’s thought. In this context, there are many bulletins carried out by geographers and non-geographers on his intellectual trajectory. However, this essay does not seek to add one more to them, but rather to argue about the passage from a philosophy of consciousness to a linguistic or intersubjective philosophy in Miltonian geographical thought. The analysis focuses on his works and articles that have been written since 1990, and whose ideas are solidified, especially in The nature of space: technique, time, reason and emotion. It starts from the assumption of his theoretical affiliation with the mentalist or subjective philosophy that has marked his theoretical-methodological framework until then. In this way, it is found that communicative or intersubjective rationality, language as a means of understanding between social actors and, consequently, communicative action, were incorporated into his critical geographic philosophy. Thus, it is concluded that Milton Santos advances in the consideration of linguistic intersubjectivity as an explanatory data of space, without abandoning, however, his anchorage in the subjective geographical philosophy.